Enterococcus avium: A Rare Opportunistic and Multidrug Resistant Pathogen in Healthcare Setting - Peetam Singh; Anita Pandey; Gaurav Saini (JK Science)
The enterococci are Gram positive and catalase negative bacteria usually inhabiting the gastrointestinal tract of animals and humans. The common species of the genus Enterococcus associated with clinical conditions are Enterococcus faecium and Enterococcus faecalis. The other species of the genus Enterococcus are rarely isolated from clinical specimens and rarely considered as pathogens. Enterococcus avium has rarely been reported causing opportunistic infections in immunocompromised individuals or persons having comorbidities and the pathogenic potential of Enterococcus avium is still debatable. We reported a series of four clinical cases due to infection with Enterococcus avium. Among these cases we reported one case of blood stream infection, one case of catheter associated urinary tract infection and two cases of peritonitis. These reported cases were associated with immunocompromised states or comorbidities. Enterococcus avium was identified by VITEK-2 Compact automated system. All of these isolates were susceptible against high end antibiotics glycopeptides and linezolid.